PENGARUH PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) DAN GAJI TERHADAP KINERJA KARYAWAN TETAP - Safirazzahra, Adelia; Setiawan, Margono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Employee performance is the work results attained by an employee from carrying out his job according to the assigned responsibility. His performance contributes his contribution to organization. Employee performance can be improved by paying attention to several factors, such as workplace safety and health and employee’s wage. The objective of this research is to identify the effects of the application of workplace safety and health program and wage on the performance of permanent employees at PT Serim Indonesia in Pasuruan. Using saturated sampling, 108 permanent employees of the company were selected to be the sample of this quantitative explanatory research. The data of this study was harvested from primary data sources, questionnaires, and library research and was analyzed using instrument test, classical assumption test, and multiple linear regression in SPSS version 26. This study finds that (1) the application of workplace safety and health program and wage simultaneously have a positive and significant effect on the performance of the permanent employees PT Serim Indonesia, that (2) the application of workplace safety and health program partially have a positive and significant effect on the employee’s performance, and that (3) wage has a positive and significant effect on the employee’s performance.